Memperkuat Keterampilan Berpikir Kreatif Melalui Model Pembelajaran Proyek Berlandaskan Metode Design Thinking - Aprianto, Muhamad Tri Panunggal; Kuswandi, Dedi; Soepriyanto, Yerry (Universitas Negeri Malang, 2023)
The design thinking method is used as the main approach in developing learning models to promote creativity and innovation in students. This model adopts the instructional design development model by Walter Dick & Lou Carey and consists of 5 stages: Discovery, Interpretation, Idea Determination, Experimentation, and Evaluation. The validity of this learning model has been verified by material experts and media experts, and the results show a high degree of suitability. Trials on large groups of students confirmed the validity and usefulness of the project learning model based on the design thinking method. The research results show that this model meets the requirements of validity, practicality, and effectiveness. Statistical analysis shows that there is a significant difference in students' creative thinking skills after applying this learning model. Trials on students indicated that the project learning model based on the design thinking method was valid and appropriate to be implemented in learning, and received positive responses from students. Therefore, this model can be applied in learning to empower students' creative thinking skills in learning media innovation courses.AbstrakMetode design thinking digunakan sebagai pendekatan utama dalam pengembangan model pembelajaran untuk menggalakkan kreativitas dan inovasi pada mahasiswa. Model ini mengadopsi model pengembangan desain instruksional oleh Walter Dick & Lou Carey dan terdiri dari 5 tahap: Penemuan, Penafsiran, Penetapan Ide, Eksperimen, dan Evaluasi. Validitas model pembelajaran ini telah diverifikasi oleh ahli materi dan ahli media, dan hasilnya menunjukkan tingkat kesesuaian yang tinggi. Uji coba pada kelompok besar mahasiswa menegaskan kevalidan dan kegunaan model pembelajaran proyek berdasarkan metode design thinking. Hasil penelitian menunjukkan bahwa model ini memenuhi persyaratan validitas, kepraktisan, dan efektivitas. Analisis statistik menunjukkan adanya perbedaan signifikan dalam keterampilan berpikir kreatif mahasiswa setelah menerapkan model pembelajaran ini. Uji coba kepada mahasiswa mengindikasikan bahwa model pembelajaran proyek berbasis metode design thinking adalah valid dan pantas diimplementasikan dalam pembelajaran, serta mendapatkan tanggapan positif dari mahasiswa. Oleh karena itu, model ini dapat diterapkan dalam pembelajaran untuk memberdayakan keterampilan berpikir kreatif mahasiswa dalam mata kuliah inovasi media pembelajaran.AbstractThe design thinking method is used as the main approach in developing learning models to promote creativity and innovation in students. This model adopts the instructional design development model by Walter Dick & Lou Carey and consists of 5 stages: Discovery, Interpretation, Idea Determination, Experimentation, and Evaluation. The validity of this learning model has been verified by material experts and media experts, and the results show a high degree of suitability. Trials on large groups of students confirmed the validity and usefulness of the project learning model based on the design thinking method. The research results show that this model meets the requirements of validity, practicality, and effectiveness. Statistical analysis shows that there is a significant difference in students' creative thinking skills after applying this learning model. Trials on students indicated that the project learning model based on the design thinking method was valid and appropriate to be implemented in learning, and received positive responses from students. Therefore, this model can be applied in learning to empower students' creative thinking skills in learning media innovation courses.